Evaluación de tres técnicas para obtención de ovocitos (aspiración folicular, slicing, exposición folicular) con dos crioprotectores (etilenglicol y polietilenglicol) en conejas (oryctolagus cuniculus) de matadero en el ceasa - Paredes Alarcón, Juan Oswaldo (2015)
In order to compare three methods of collection (follicular aspiration, slicing and follicular exposure) oocytes with two cryo-protectants (ethylene glycol and polyethylene glycol) these oocytes were obtained from ovaries of females Oryctolagus cuniculus sacrificed. The transfer took place in a thermos with sodium chloride 0.9% over a period of 2 hours. Three techniques were used to extract the oocytes, in oocyte; the bevel of the syringe was introduced into each follicle aspiration for continuing to the deposit of the follicular fluid in a Petri dish through the Holding mean to identify oocytes....